ADAM10 and ADAM17 cleave PD-L1 to mediate PD-(L)1 inhibitor resistance. (1st January 2020) - Orme, Jacob J.; Jazieh, Khalid A.; Xie, Tiancheng; Harrington, Susan; Liu, Xin; Ball, Matthew; Madden, Benjamin; Charlesworth, M. Cristine; Azam, Tariq U.; Lucien, Fabrice; Wootla, Bharath; Li, Yanli; et al.
ABSTRACT: ADAM10 and ADAM17 expression and soluble PD-L1 (sPD-L1) predict poor prognosis in many malignancies, including in patients treated with PD-(L)1 inhibitors. The mechanism of soluble PD-L1 production and its effects are unknown. Here we uncover a novel mechanism of ADAM10- and ADAM17-mediated resistance to PD-(L)1 inhibitors. ADAM10 and ADAM17 cleave PD-L1 from the surface of malignant cells and extracellular vesicles. This cleavage produces an active sPD-L1 fragment that induces apoptosis in CD8 + T cells and compromises the killing of tumor cells by CD8 + T cells. Reduced tumor site PD-L1 protein-to-mRNA ratios predict poor outcomes and are correlated with elevated ADAM10 and ADAM17 expression in multiple cancers. These results may explain the discordance between PD-L1 immunohistochemistry and PD-(L)1 inhibitor response. Thus, including ADAM10 and ADAM17 tissue staining may improve therapy selection. Furthermore, treatment with an ADAM10/ADAM17 inhibitor may abrogate PD-(L)1 inhibitor resistance and improve clinical responses to PD-(L)1 immunotherapy.